Clinical Features of Patients presented with Extra Dura Haematoma Attended at a Tertiary Care Hospital in Dhaka City (Bangladesh Journal of Neurosurgery, 2020)
Background: The clinical presentation of head injury may vary.Objective: The purpose of the present study was to see the clinical features of patients presented with extra dural haematoma.Methodology: This cross-sectional study was conducted in the Department of Neurosurgery at Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2010 to June 2011 for a period of one year and six months. All patients who underwent surgery with traumatic head injury having extradural haematoma were included in the study. The clinical features of the patients were recorded.Result: Eighty (80) patients of traumatic head injury within and after 24 hours of head injury were enrolled in this study. In this study unconsciousness was in 32(40.0%) cases. However, convulsion was found in 12 (15.0%). Vomiting was the most common presenting features which was 71(88.7%) cases. Headache was reported in 48(60.0%) cases. The normal pupillary response was found in 42(52.5%) cases. The rest 38(47.5%) cases were dilated pupil.Conclusion: In conclusion vomiting is the most common clinical features of patients presented with extra dura haematemases vomiting followed by unconsciousness and headache.Bang. J Neurosurgery 2020; 9(2): 126-129